(untitled) (Biological Sciences - PJSIR, 2003)
The complex dielectric constant of ethyl alcohol, methyl alcohol and 1- propanol and their mixtures with water of different concentration, (0 to 100% by weight ) at the temperature of 303K has been evaluated ,within the frequency range of (100KHz- 100 MHz). Moreover, the viscosity h of each alcohol and its mixture with water have been measured at this temperature. The dielectric properties have been evaluated by Hartshorn and Ward apparatus. The purpose of this work is to study the influence of aliphatic group, size and shape on the extent of hydrogen bonding and also to obtain the thermodynamic data on hydrogen bond formation in the pure liquid state and its mixture. The width of the semicircle plot determines the distribution of average relaxation time. Dielectric relaxation time in pure alcohols and their water mixture has been calculated from the respected Cole-Cole plot and dielectric data. A single relaxation time of 117.16ps has been obtained for the molecules of pure methanol, whereas, the dielectric data of prophyl alcohol which indicates the viscosity h of each alcohol and its mixture with water have been measured at the temperature 303 K. The dielectric properties in distribution of relaxation time, which is in good agreement with the Davidson-Cole representation. The molecules in liquid mixture within frequency range, the mixture has more than one relaxation time, leading to the shortening of main relaxation time as compared with the pure alcohol and broadening of the complex permitivity spectra. The dependence of the dielectric relaxation on composition shows a remarkable behavior. Results are discussed in the light of H-bonded molecules.